2022
DOI: 10.1039/d1cy02361f
|View full text |Cite
|
Sign up to set email alerts
|

Carbene-like reactivity of methoxy groups in a single crystal SAPO-34 MTO catalyst

Abstract: Synchrotron FTIR microspectroscopy coupled with mass spectrometric analysis of desorbed products has been used to investigate the initial stages of the methanol to olefins (MTO) reaction in single crystals of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…After that, Chowdhury et al again identified surface carbenoid species, using dynamic nuclear polarization surface-enhanced NMR spectroscopy (DNP SENS), on the post-MTH reacted zeolite ZSM-5 (Figure d) . In recent years, Howe and colleagues also studied the fate of SMS to understand initial events in MTH catalysis over zeolites (ZSM-5 and SAPO-34) with the help of synchrotron infrared microspectroscopy. , Upon their investigations with labeled methanol (CD 3 OH), they detected the formation of zeolite OD groups (Z-O-D), which was indicating the CD bond breakage of labeled SMS and formation of carbene-like species. In general, during investigations on the presence of carbenes in MTH, one should pay special attention to zeolite topologies, and their pore/cage dimensions as well, because confinement effects can change the stability of formed carbenes and their contribution to the whole mechanism.…”
Section: Carbene Chemistry In Zeolite Catalysismentioning
confidence: 99%
“…After that, Chowdhury et al again identified surface carbenoid species, using dynamic nuclear polarization surface-enhanced NMR spectroscopy (DNP SENS), on the post-MTH reacted zeolite ZSM-5 (Figure d) . In recent years, Howe and colleagues also studied the fate of SMS to understand initial events in MTH catalysis over zeolites (ZSM-5 and SAPO-34) with the help of synchrotron infrared microspectroscopy. , Upon their investigations with labeled methanol (CD 3 OH), they detected the formation of zeolite OD groups (Z-O-D), which was indicating the CD bond breakage of labeled SMS and formation of carbene-like species. In general, during investigations on the presence of carbenes in MTH, one should pay special attention to zeolite topologies, and their pore/cage dimensions as well, because confinement effects can change the stability of formed carbenes and their contribution to the whole mechanism.…”
Section: Carbene Chemistry In Zeolite Catalysismentioning
confidence: 99%
“…Several mechanisms have been used to describe the induction period of the methanol-to-olefin conversion over zeolite catalysts. These include: (1) carbene, (2) carbon monoxide, (3) methane-formaldehyde, and (4) methoxymethyl cation. , Each mechanism involves a similar set of steps, namely: adsorption and desorption of methanol, dimethyl ether, and water, olefin (ethylene and/or propylene) formation, and release. These adsorption and desorption steps occur as the catalysts evolve from fresh catalysts to working catalysts at steady-state.…”
Section: Resultsmentioning
confidence: 99%
“…Monitoring the IR spectra of samples obtained during the reaction of surface-bound deuterated methoxy (OCD 3 ) with ethene at 250 °C over ZSM-5 indicated that the intensities of the C-D stretching bands decreased while a peak related to an acidic O-D group appeared at 2655 cm -1 and increased in intensity, demonstrating the attachment of a D atom to a neighboring O [42] . Additional evidence for this process was obtained by reacting OCD 3 with DME at 200 °C [43] . In 2016, Chowdhury et al provided further support for the carbene mechanism on the basis of analyses by two-dimensional magic angle spinning 1 H- 13 C and 13 C- 13 C solid-state NMR spectroscopy [36] .…”
Section: Carbene Mechanismmentioning
confidence: 91%